1 EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENINGKATKAN DISIPLIN BELAJAR SISWA SMP KOTA SEMARANG - Setyawan, David Ari (Universitas Nusantara PGRI Kediri, 2016)
ABSTRACT The purposes of this research are: (1) Determine the implementation guidance for the group was held in Junior High School Semarang; (2) Examining of learning discipline level (3) The discovery of the model development group counseling services with self-management techniques to improve discipline of students’ learning; (4) determine the effectiveness of the model development group counseling services with self-management techniques to improve discipline of students’ learning. Methods This study was conducted by the Research and Development (R & D) withthe following steps: (1) preparation of model development, (2) formulating hypothetical model, (3) feasibility test of hypothetical model, (4) improvement of hypotetical model, (5) field test, (6) the end result ot the product. Generating a model of group counseling by self management techniques to improve students learning discipline. Key words: Learning discipline, group guidance, self management.